Do field position and playing standard influence athlete performance in wheelchair basketball? - de Witte, A. M. H.; Hoozemans, M. J. M.; Berger, M. A. M.; van der Woude, L. H. V.; Veeger, D. H. E. J. (Journal of Sports Sciences, 2016)
Improved understanding of mobility performance in wheelchair basketball is required to increase game performance. The aim of this study was to quantify the wheelchair-athlete activities of players in different field positions and of different playing standard during wheelchair basketball matches. From video analysis, absolute and relative duration and frequency of wheelchair movements and athlete control options were examined in 27 national standard and 29 international standard players during entire wheelchair basketball matches. Between-group factorial analysis of variances identified that national players drove more forward (42.6 ± 6.8 vs. 35.4 ± 3.7%; effect size Cohen`s d (ES) = 1.48) and started more often driving forward (33.9 ± 2.6 vs. 31.8 ± 2.8; ES = 0.77) during a match while the mean activity duration for a single driving forward activity was longer (4.3 ± 0.9 vs. 3.7 ± 0.6 s; ES = 0.75) than for international players. Furthermore, national players performed fewer rotational movements (21.8 ± 4.0 vs. 28.9 ± 7.8%; ES = -1.30) and started less often with the rotational movements (35.0 ± 3.6 vs. 40.5 ± 5.5; ES = -1.21) while the mean activity duration for a single rotation activity was shorter (2.1 ± 0.3 vs. 2.3 ± 0.3 s; ES = -0.67) than for international players. Differences in mobility performance among guard, forward and centre players were minimal. The results should help wheelchair basketball coaches specify wheelchair-handling training techniques and means to optimise wheelchair-athlete configurations.